Using regumate to control estrus in swine - Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 2004)
Altrenogest, marketed for use in horses as Regumate, is a synthetic progestin that is marketed for use in pigs as MATRIX. It effectively regulates the occurrence of estrus in randomly cycling gilts if it is provided for 14 or more days at a daily dose of 15 mg/day. It is important to assure that each gilt receives her full dose; otherwise problems of cystic follicles and reduced fertility may be observed.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Pigs; Estrous synchronization; Altrenogest; Swine